Urban development with financially sustainable bus transit service - a case study - Ng, Tze Seng. (2011)
The positive correlation between urban population density and transit service patronage is well observed, as was developed via statistical approaches in previous studies. High population density provides an adequate environment for the bus transit service to be financially sustainable. In this study, we seek to derive the relationship between urban development population density and the financial sustainability of bus transit service. Two study areas are chosen, whose population percentages are relatively similar. Trip generated from the region to the nearby areas are assumed to be served by either the buses or the rail service. The transportation model that was created from the study of these two areas could then be used to analyse other areas. The sensitivity of urban development density on the financial sustainability of the bus service is also studied via the examination of frequency. Through this study, the threshold urban density of the areas could be determined, below which the service could no longer be sustained financially. The results provide a guideline for planning urban development with financially sustainable bus service.